Pengaruh Recruitment Strategy, Selection Proses, Dan Onboarding Program Terhadap Employee Performance Hotel Madeline Kota Bengkulu - Putri, Sarah Sephia; Hidayati, Arifah; Waliamin, Janusi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to determine the influence between X1 (Recruitment Strategy), X2 (Selection Process), X3 (Onboarding Program) on Y (Employee Performance). This study is explanatory research to determine the influence between independent variables and dependent variables. The sample in this study amounted to 34 people, taken using the Total Sampling technique. where the entire population became the research sample. Data collection using a questionnaire. The analysis technique used to see whether or not there is an influence is the Hypothesis test (t Test and F Test) to see the magnitude of the influence the researcher used the Correlation Test. The results of this study are: Recruitment Strategy has a significant effect on Employee Performance with a fairly strong degree of relationship, Selection Process has a significant effect on Employee Performance with a low degree of relationship, Onboarding Program has a significant effect on Employee Performance with a fairly strong degree of relationship and the results of the F test between the Recruitment Strategy, Selection Process and Onboarding Program variables have a significant effect on Y Employee Performance